PEMBERDAYAAN MASYARAKAT PADA DESA WISATA KANDRI KECAMATAN GUNUNG PATI KOTA SEMARANG - Amalia Hani Rahmawati; Hardi Warsono; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Jatibarang dam construction in 2010 made an impact on the livelihoods of Kandri Village’s communities who has majority as farmers because of several hectares of agricultural land sunk into the reservoir. Kandri village’s communities who are affected by the construction of Jatibarang reservoirs need to prepare themself because the impact of dam construction with community empowerment. This research aim to describe the forms, the results, and identifying constraints on community empowerment Kandri Tourism Village. The method in this research is taxonomy analysis of the overall data with detailed focus on a particular domain that is useful to describe the phenomenon or problem of the study. The results showed that the forms of community development in the Kandri Tourism Village are culinary, crafts, and special interest education. Empowerment results in this research which are community needs, the range of productive resources, and the level of community participation are not maximized. The community development constraints in Kandri Tourism Village are constraints of the individual which have a lack of stability of business, leading commodities were stopped when there is a loss, there is still a dependency with outsiders, lack of confidence, and concerns about insecurity, while the constraint of the social system is obstacles of interest groups.